THE EFFECT OF ENVIRONMENTAL MANAGEMENT SYSTEM ON FIRM PERFORMANCE WITH CAPITAL STRUCTURE AS MODERATING VARIABLE - Sijabat, Destri Syeba Stevani; Hutabarat, Francis; Siagian, Harlyn (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study aims to analyze the effect of Environmental Management Systems (EMS), measured through ISO 14001 certification, on Company Performance, measured by Return on Equity (ROE), with Capital Structure, measured by Debt to Equity Ratio (DER), as a moderating variable. Using secondary data from 36 manufacturing companies listed on the MNC-36 Index of the Indonesia Stock Exchange during the period 2018-2023, the analysis was conducted through moderation regression and a simple slope test. The findings show that SML has a significant positive effect on ROE, where DER moderates this relationship non-linearly: negatively at low DER levels (Estimate = -8.82, p < 0.001), insignificantly at average DER levels (Estimate = 1.36, p = 0.392), and positive at high DER levels (Estimate = 11.54, p< 0.001). These results are in line with Stakeholder Theory and Agency Theory, and provide practical implications for managers to optimize capital structure before implementing EMS.